Cooperative CO2 adsorption mechanism in a perfluorinated CeIV-based metal organic framework. Issue 11 (17th February 2023) - Cavallo, Margherita; Atzori, Cesare; Signorile, Matteo; Costantino, Ferdinando; Venturi, Diletta Morelli; Koutsianos, Athanasios; Lomachenko, Kirill A.; Calucci, Lucia; Martini, Francesca; Giovanelli, Andrea; Geppi, Marco; Crocellà, Valentina; et al.
Abstract : The peculiar mechanism of cooperative CO2 adsorption in a perfluorinated Ce IV -based metal–organic framework with MIL-140 topology is disclosed using a combination of experimental and computational methods. Abstract : Adsorbents able to uptake large amounts of gases within a narrow range of pressure, i.e., phase-change adsorbents, are emerging as highly interesting systems to achieve excellent gas separation performances with little energy input for regeneration. A recently discovered phase-change metal–organic framework (MOF) adsorbent is F4_MIL-140A(Ce), based on Ce IV and tetrafluoroterephthalate. This MOF displays a non-hysteretic step-shaped CO2 adsorption isotherm, reaching saturation in conditions of temperature and pressure compatible with real life application in post-combustion carbon capture, biogas upgrading and acetylene purification. Such peculiar behaviour is responsible for the exceptional CO2 /N2 selectivity and reverse CO2 /C2 H2 selectivity of F4_MIL-140A(Ce). Here, we combine data obtained from a wide pool of characterisation techniques – namely gas sorption analysis, in situ infrared spectroscopy, in situ powder X-ray diffraction, in situ X-ray absorption spectroscopy, multinuclear solid state nuclear magnetic resonance spectroscopy and adsorption microcalorimetry – with periodic density functional theory simulations to provide evidence for the existence of a unique cooperative CO2 adsorption mechanism in F4_MIL-140A(Ce). Such mechanism involves the concerted rotation of perfluorinated aromatic rings when a threshold partial pressure of CO2 is reached, opening the gate towards an adsorption site where CO2 interacts with both open metal sites and the fluorine atoms of the linker.